2023
DOI: 10.21203/rs.3.rs-2275950/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Bone marrow mesenchymal stem cell exosomes attenuate neuroinflammation after diabetic intracerebral hemorrhage via miR-129-5p/HMGB1

Abstract: Background In this study, we investigated whether mesenchymal stem cell (MSC)-derived exosomes (Exos) could regulate hyperglycemia-induced neuroinflammation by transferring microRNA-129-5p (miR-129-5p). Methods Bone marrow-derived MSC (BMSC)-Exos were isolated from media BMSCs from mice. This was followed by transfection with miR-129-5p. BMSC-Exos or miR-129-5p-overexpressing BMSC-Exos were intravitreally injected into diabetic mice with intracerebral hemorrhage (DM/ICH) for in vivo analyses and were cocultu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 56 publications
0
0
0
Order By: Relevance
“…Among the up-regulated differentially expressed miRNAs, miR-150-5p ranked second, which was previously reported to regulate macrophages polarization. Although first detected in chronic lymphocytic leukemia, recent reports have indicated that miR-150-5p is associated with the activation and differentiation of macrophages (47)(48)(49). Indeed, we validated that miR-150-5p was highly expressed in LPS-Exo versus Exo, and transfection of miR-150-5p inhibitors into BMDMs reversed the effect of LPS-Exo on the activation and polarization of macrophages.…”
Section: Discussionsupporting
confidence: 62%
“…Among the up-regulated differentially expressed miRNAs, miR-150-5p ranked second, which was previously reported to regulate macrophages polarization. Although first detected in chronic lymphocytic leukemia, recent reports have indicated that miR-150-5p is associated with the activation and differentiation of macrophages (47)(48)(49). Indeed, we validated that miR-150-5p was highly expressed in LPS-Exo versus Exo, and transfection of miR-150-5p inhibitors into BMDMs reversed the effect of LPS-Exo on the activation and polarization of macrophages.…”
Section: Discussionsupporting
confidence: 62%
“…Among the up-regulated differentially expressed miRNAs, miR-150-5p ranked second, which was previously reported to regulate macrophages polarization. Although first detected in chronic lymphocytic leukemia, recent reports have indicated that miR-150-5p is associated with the activation and differentiation of macrophages (47)(48)(49). Indeed, we validated that miR-150-5p was highly expressed in LPS-Exo versus Exo, and transfection of miR-150-5p inhibitors into BMDMs reversed the effect of LPS-Exo on the activation and polarization of macrophages.…”
Section: Discussionsupporting
confidence: 62%